The Evolution of Matter: From the Big Bang to the Present Day Earth - Tolstikhin, I. N (Cambridge University Press, 2013)
This book is a cross between a textbook and a monograph, and it was started as an attempt to link depth with breadth in cosmo- and geochemistry. The need for this becomes obvious when one sees the two opposing trends in this science. On the one hand, much excellent research goes into great depth in a relatively narrow field, unnoticed except by specialists and, on the other hand, wide-ranging textbooks capture the imagination of a broader audience but cannot do justice to the actual data-gathering and interpretation. Thus, if one is interested in cosmochemistry, or the solar system or planetary formation and evolution, one can readily find a number of specific, well-written, textbooks